Peran perbankan syariah terhadap pembiayaan kepemilikan rumah - Nurkhalifah, Nurkhalifah; Nyrvana, Syarifah Rara Warda (Maliki Interdisciplinary Journal, 2024)
The purpose of this article is to discuss the role of Islamic banking in mortgage financing. Through a literature study method based on analyzed sources, this article discusses the role played in mortgage financing under Islamic principles. This article discusses the advantages and disadvantages of the contracts used in this financing from several sources that have been obtained and processed again. Sharia banking has an important role in helping customers with home ownership by providing financing and agreed payment methods. In conclusion, this article discusses the role of Islamic banking in mortgages with Islamic principles to help customers in need. From the results obtained, this mortgage is very helpful for customers in home financing.